A Few Remarks Towards Environmental Aesthetics. Aesthetics of Landscapes and its Impact on Human Emotions - Kišoňová, Renáta (Studia Ecologiae et Bioethicae, 2022)
The following paper focuses on the current meaning of environmental aesthetics and the aesthetics of landscapes. Its purpose is to show the relationship of human artificial living to natural living and human health as well as aesthetic and social emotions depending on health landscapes. There is the terms “environmental aesthetics” and “aesthetics of landscapes” are analysed in the broader philosophical and interdisciplinary context of Norberg-Schulz’s theory of architecture, Konrad Lorenz’s theory of ethology, and Wolfgang Welsch’s transhuman aesthetics. What are the mechanisms of a human relating to a landscape? What mechanisms of our emotionality are related to a devastated or healthy landscape? These are the central questions of the following consideration. The methods used in my research are analyses, etymology, the phenomenology of emotionality, and phenomenology of the landscape. The primary and expected findings are that people appreciate and enjoy scenic landscapes to satisfy their emotionality, cooperation, and well-being. Conclusion: Landscapes create our identification, surroundings which create our feelings, experiences, and emotions. A good example of such a relationship are inhabitants of today’s uninhabited islands who were not able to cooperate, who destroyed their environment, destabilized and deforested their surroundings up to their complete extinction.